1989
DOI: 10.1017/s002185960007009x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional availability of amino acids from the rumen anaerobic fungusNeocallimastixsp. LM1 in sheep

Abstract: SUMMARYThe rumen anaerobic fungusNeocallimastixsp. LM1 was specifically labelled in batch culture with either [14C]lysine, [14C]lysine + [3H] tyrosine, [14C] methionine, or [35S] sulphide. Fractionation of acid hydrolysates of fungal biomass on an amino acid analyser showed that the labelled amino acids were directly incorporated into fungal protein with little or no degradation. [35S] Sulphide was incorporated into cysteine and methionine.Absorption of amino acids from the small intestine was measured in shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Anaerobic fungal proteases provide amino acids for fungal growth, as well as aiding the penetration of plant material. In addition to producing enzymes, anaerobic fungi themselves contribute to the protein supply of the host by serving as a source of high‐quality microbial protein, that is synthesised in the rumen, passing to the abomasum and intestines for subsequent digestion and absorption by the host (Kemp et al ., ; Gulati et al ., ; Atasoglu & Wallace, ).…”
Section: Significance For Other Gut Microorganism and The Hostmentioning
confidence: 99%
“…Anaerobic fungal proteases provide amino acids for fungal growth, as well as aiding the penetration of plant material. In addition to producing enzymes, anaerobic fungi themselves contribute to the protein supply of the host by serving as a source of high‐quality microbial protein, that is synthesised in the rumen, passing to the abomasum and intestines for subsequent digestion and absorption by the host (Kemp et al ., ; Gulati et al ., ; Atasoglu & Wallace, ).…”
Section: Significance For Other Gut Microorganism and The Hostmentioning
confidence: 99%
“…Besides producing proteases, AF directly contribute to protein supply of the host in terms of being part of the microbial biomass that passes down to the intestines from rumen, for subsequent digestion and absorption. Gulati et al (1989) showed that AF cells were composed of proteins with a well-balanced combination of amino acids that were highly available to the ruminant host. A high proportion of the protein components of three monocentric AF (i.e., Neocallimastix sp.…”
Section: Anaerobic Fungi As Feed Additives To Promote Animal Health Amentioning
confidence: 99%
“…They are characterized by a high lysine content as compared with rumen bacterial proteins (Onoda et al, 1993). Moreover, fresh rumen fungi infused into the abomasum are extensively digested (Gulati et al, 1989). These findings suggest that the rumen fungi may substantially contribute to the amino acid supply for their host animals if notable amounts of fungi are transferred from the rumen to the lower gut.…”
Section: Introductionmentioning
confidence: 98%
“…Orpin and Greenwood (1986) demonstrated that amino acid supplements to the defined minimal medium (consisting of ammonium ion, haemin, vitamins and a reduced source of sulphur) greatly stimulate the growth of Neocallimastix patriciarum. The rumen fungi Neocallimastix sp can take up amino acids and incorporate them into proteins without requiring any modification of the amino acids (Gulati et al, 1989). When a mixture of L-(U-!4C) amino acids was added to cultures of rumen fungi, the radioactivity was later found located in the cellular proteins, lactate, volatile fatty acids and ethanol (Marounek and Vovk, 1992 (1989,1992) (1981) for 3 days and then zoospores were harvested anaerobically by filtrating the cultures through nylon meshes (10 0 pm).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation